Pengaruh Model Kepemimpinan dan Motivasi Kerja Terhadap Kinerja Pegawai Aparatur Sipil Negara - Achmad Mutohar (Ecobuss, 2021)
The focus of this research is the influence of leadership models and work motivation on the performance of civil servants in the state. This research was conducted at the Sukomanunggal office, Surabaya, East Java. The research was conducted from May to July 2019. The type of research was primary data using a questionnaire. The population in this study includes 30 civil servants of the Sukomanunggal sub-district, Surabaya, who are also the sample in this study. The result shows that partially the leadership model variable and the work motivation variable have a significant effect on employee performance, and simultaneously the independent variable also has a significant effect on the dependent variable with a sig of 0,000. With multiple linear regression analysis Y = 0,531 + 0,375X1 + 0,454X2 + 2. As well as the coefficient of determination of 55,7%, while the remaining 44,3% is influenced by other factors outside the X variable used. Keywords: Leadership Model, Work motivation, Employee Performance